Structural Equation Modeling Pada Adopsi Sistem Informasi Akuntansi Berbasis E-Commerce Menggunakan UTAUT2 - Widya Reza; Faradiba Jabnabillah; Andini Setyo Anggraeni (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Batam City MSME players still encounter obstacles in the adoption of e-commerce-based Accounting Information Systems (AIS). This study aims to analyze the factors that influence the adoption of an e-commerce-based accounting information system for MSMEs in Batam City using the UTAUT2 model by considering cultural factors. The data used in this study is primary data obtained through a survey of MSME actors in Batam City using a questionnaire with the purposive sampling method. The sample used was 150 MSME actors. Hypothesis testing is carried out using Structural Equation Modeling (SEM) using SmartPLS. The results of the study proved that facilitating conditions, habits and behavioural intentions affect the use behavior variable directly. Cultural factors of individualism collectivism, uncertainty avoidance and long term orientation also succeeded in moderating the influence of behavioural intention variables on use behavior. The results of this study imply that the government can consider cultural factors in developing a strategy to increase the adoption of MSME e-commerce accounting information systems in Batam City to improve business performance. Keywords: SEM, AIS, E-commerce, UTAUT2